PENSAMENTO MÉDICO E HISTÓRIA: UM BREVE ENSAIO (Revista de História Regional, 2007)
This article considers the process of the construction of the medical representations as a scientific elaborated knowledge. In this sense, based on the reflections of Ernest Cassirer and Michel Foucault the author takes as his object of analysis the construction of homeopathic medicine among the medical tendencies in he 19th century.